Surveillance of health and primary care of asylum seekers in reception centers: concept and results. (13th November 2019) - Jahn, R; Bozorgmehr, K
Abstract: Background: Reliable data on health and primary care among asylum seekers in reception centers are essential for the planning and provision of medical services, but haphazard care provision and lack of standards for health information systems in these centers preclude routine health monitoring. We aimed to establish a routine surveillance system in reception centers for asylum seekers in Germany, generating multi-center data on key health indicators. Methods: To enable routine health surveillance, we established an electronic medical records system (RefCare©), a research network, and an IT-infrastructure for the automated analysis of health data in German reception centers. Within the network, 64 health and health care indicators on morbidity, care processes, quality of care and syndromic surveillance were identified. In November 2018, we analyzed 33 indicators using routine health data from nine centers in three federal states. We calculated single-center prevalence and pooled estimates for selected morbidity indicators stratified by age and sex, and process and quality indicators stratified by center. Results: A total of 8, 406 patients and 39, 449 patient contacts were analyzed, with mean utilization of health services ranging from 2.33 (Standard deviation, SD: 2.0) to 11.49 (SD: 22.82). The morbidities with the highest prevalence were respiratory, digestive and certain infectious diseases, followed by consequences of external causes, musculoskeletal and mental health conditions. Irrational use of antibiotics was below the threshold for primary care settings. Conclusions: For the first time in Germany, a harmonized infrastructure for the automated, anonymized surveillance of the health and health care of asylum seekers in reception centers was established in several federal states. The analysis of morbidity indicators shows a primary care-typical disease profile, with special needs regarding mental health and consequences of external causes, such as physical trauma. Key messages: Routine health surveillance of asylum seekers in reception centers can be achieved through an innovative harmonized, cross-regional, multi-center, anonymous and automated surveillance system. Health issues of asylum seekers in reception centers in Germany mainly consist of primary care conditions with special vulnerabilities regarding mental health and consequences of external causes.